Pengaruh Orientasi Pasar dan Manajemen Pengetahuan Terhadap Kinerja Pemasaran - Nurtiah Nurtiah (Faculty of Economic and Business, 2016)
The Influence of Market Orientation and Knowledge Management to Marketing PerformanceThe purpose of this study was to analyze the effect of market orientation and knowledge management performance of marketing in District of Ciomas and Dramaga Bogor. Analysis tools used in this study is Structural Equation Modeling (SEM). The results of the analysis was as follows: the value of market orientation variable towards innovation resulted p value which was greater than the lowest average value. The value of knowledge management variable towards competitive advantage resulted p value, which was greater than the lowest average value. The value of innovation variable towards competitive advantage resulted p value, which was smaller than the lowest average value. The value of innovation variable towards marketing performance resulted p value which was greater than the lowest average value. The value of competitive advantage variable towards marketing performance resulted p value which was smaller than the lowest average value.DOI: 10.15408/ess.v6i2.3775